Clinical outcome and prognostic factors in hepatocellular carcinoma patients with bone metastases medicated with zoledronic acid. Issue 10 (8th December 2016) - Honda, Yohji; Aikata, Hiroshi; Honda, Fumi; Nakano, Norihito; Nakamura, Yuki; Hatooka, Masahiro; Morio, Kei; Kobayashi, Tomoki; Fukuhara, Takayuki; Nagaoki, Yuko; Kawaoka, Tomokazu; Hiramatsu, Akira; et al.
Abstract: Aims: We retrospectively analyzed the clinical outcome and prognostic parameters in patients with hepatocellular carcinoma (HCC) and bone metastases who had received treatment with zoledronic acid (ZOL). Methods: Ninety‐nine HCC patients with bone metastases who had been treated with ZOL were enrolled in this retrospective cohort study. We analyzed the prognostic factors, including serum N‐telopeptide of type I collagen (NTX) levels, as bone metabolism markers. Results: The median overall survival (OS) time was 11.5 months. Child–Pugh grade A ( P = 0.004) and intrahepatic tumor stage (IHTS) T0–3 ( P = 0.010) correlated significantly with favorable OS. In 46 patients with grade A and T0–3, receiver operating characteristic curve analysis defined 16 nmol BCE/L serum NTX as the cut‐off level for median OS. Multivariate analysis identified baseline serum NTX <16 nmol BCE/L ( P = 0.045) as the only significant and independent determinant of OS. Conclusion: Low baseline serum NTX level correlated with favorable outcome in bone metastatic HCC patients with Child–Pugh grade A and IHTS T0–3 treated with ZOL.